2015
DOI: 10.1038/hr.2015.96
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in meteorological parameters and office, ambulatory and home blood pressure: predicting factors and clinical implications

Abstract: This study investigated the relationship between seasonal variations in blood pressure (BP) and the corresponding changes in meteorological parameters and weather-induced patients' discomfort. Hypertensives on stable treatment were assessed in winter-1, summer and winter-2 with clinic (CBP), home (HBP) and 24-hour ambulatory BP (ABP). Discomfort indices derived from temperature, humidity and atmospheric pressure that reflected subjects' discomfort were evaluated. Symptomatic orthostatic hypotension was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 31 publications
(48 reference statements)
2
25
1
1
Order By: Relevance
“…32 Seasonality is mainly influenced by climate changes including temperature, atmospheric pressure (AP), humidity and other meteorological variables. There is much evidence that seasonal meteorological variables influence blood pressure in both hypertensive and normotensive individuals, [33][34][35] and decreased outdoor temperature is in some way accompanied by increased intravascular systolic pressure. 36 Changes in AP may increase transmural arterial stress by transiently lowering tissue pressure with respect to blood pressure, creating a net expansive force.…”
Section: Discussionmentioning
confidence: 99%
“…32 Seasonality is mainly influenced by climate changes including temperature, atmospheric pressure (AP), humidity and other meteorological variables. There is much evidence that seasonal meteorological variables influence blood pressure in both hypertensive and normotensive individuals, [33][34][35] and decreased outdoor temperature is in some way accompanied by increased intravascular systolic pressure. 36 Changes in AP may increase transmural arterial stress by transiently lowering tissue pressure with respect to blood pressure, creating a net expansive force.…”
Section: Discussionmentioning
confidence: 99%
“…18 Regarding seasonal variations in HBP, Stergiou et al investigated seasonal BP changes by assessing HBP measurements in patients with treated hypertension in relation to changes in several meteorological parameters and weather-induced discomfort. 19 They showed that HBP was lower in the summer than in the winter and that seasonal changes in temperature and meteorological parameters that reflected weather-induced patient discomfort were correlated with HBP changes.…”
Section: Discussionmentioning
confidence: 99%
“…While awake BP is affected by various environmental factors, nocturnal BP is not. Recently, Stergiou and colleagues reported that all clinic, home, or ambulatory BP readings were affected by seasonal changes, except for nighttime BP. Nocturnal BP may be the most reproducible physiological and “real” phenotype of individual BP among all BP indices.…”
Section: Position Of Abpm In Hypertension Guidelinesmentioning
confidence: 99%